Kajian Efisiensi Penggunaan Lahan dan Pola Persebaran Perumahan di Ibukota Kabupaten Purwakarta - Martanto, Arif (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Purwakarta Cityâ€™s housing sector is growing rapidly. The demand for land for housing has become a serious challenge as the city must face increasing population. The study employs descriptive-quantitative method to explain the developments in housing, regarding the area, location and spread pattern periodically until 2010. Land use intensity analysis investigates the efficiency of land utility through examinations of building density and building coverage. Nearest neighbour analysis was employed to discover the housing pattern through the calculation of the nearest neighbor parameter in the study area. Supply and demand analysis was carried out to measure the level of availability of housing in 2010. Mapping overlay showed that housing development in the last 23 years to the year 2010 has caused land use conversions, comprising 2,57% (118,76 Hectares) into building lots, 2,23% (103,33 Hectares) into housing facilities and infrastructures, and 0,11% (5,16 Hectares) into publicÂ burial grounds. Urban spatial expression model analysis showed that Purwakarta City is expanding with a star-shaped pattern. Analysis also found 38 housing areas which were unevenly spread in a random pattern with T (nearest neighbor index) of 1,05.Â Land use intensity analysis showed that only 6 housing uses its land efficiently. Analysis also found that in2010 in Purwakarta City, there has been a housing availability backlog of 13.642 units.